Unusual presentation of retroperitoneal teratoma - Masrani, Neha N.; Shaikh, Shifa P.; Sisodiya Shenoy, Neha; Gandhi, Suraj R.; Shetty, Shravya S.; Shah , Hemanshi S. (International Surgery Journal, 2025)
Mature teratoma are usually slow growing tumours often silent in nature. We report a 1-year-old dengue positive female child with a sudden increase in size of a previously non palpable abdominal lump. After investigation and exploration, it was found to be a retroperitoneal mature cystic teratoma, which did not show any features of malignant transformation, tumour rupture, haemorrhage or infection. Most retroperitoneal teratomas are benign in nature diagnosed preoperatively but rarely there can be dilemma in establishing the diagnosis. In ambiguous cases intra operative findings or histopathology reveals final confirmatory diagnosis.